(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The results of prolonged influence of low temperatures on 51 varieties of Japanese persimmon (Diospyros kaki L.) in a new introduction area as NBG-NSC scientific farm, Novaya Kakhovka, Kherson region – are reported.